Божественні енергії та богословський метод у вченні св. Григорія Палами - Hupalo, Mariia (Vox Patrum, 2018)
Gregory Palamas’ theory of divine uncreated energies is closely connected with his defence of Hesychastic prayer and mysticism of the Tabor light. His first and immediate goal was to articulate the possibility of theosis and participation in divine life and glory as well as the chance for a man to become God-like, though not in his essence, but by God’s grace. Mysticism and doxology, communion with God is for Palamas the only adequate context of God’s self-manifestation and man’s reception of this self-presenting. This article is aiming at presenting some glimpses at the personalist and existential aspects of St. Gregory Palamas’ theology on the essence-energies distinction and Hesychast experience of the uncreated light.